Changes in Cerebrospinal Fluid Tau and β-Amyloid Levels in Diabetic and Prediabetic Patients: A Meta-Analysis - Lu, Yanhui; Jiang, Xinjun; Liu, Shuling; Li, Mingzi (Frontiers in Aging Neuroscience, 2018)
Increased risks for Alzheimer’s disease (AD) are a well-recognized consequence of diabetes, insulin resistance (IR) and hyperinsulinemia. Because cerebrospinal fluid (CSF) is surrounding the central nervous system, alterations of β-amyloid (Aβ) and tau protein in the CSF may be indicative of AD-type degenerations in the brain. Current laboratory diagnosis of AD uses three biomarkers in CSF: Aβ1-42, total tau (t-Tau), and phosphorylated tau (p-Tau). However, changes of these biomarkers in diabetic and pre-diabetic patients are scattered and variable in literature. Thus, we attempt to perform a systematical analysis of these available data. MEDLINE, EMBASE, the Cochrane Central database, China National Knowledge Infrastructure (CNKI), and Wanfang Data electronic databases were queried to gather published studies that have evaluated the AD-type biomarkers in the CSF of subjects with diabetes, IR or hyperinsulinemia in comparison with respective controls. Overall analysis of the published data showed no significant differences in Aβ1-42, t-Tau and p-Tau levels in the CSF between the (pre)diabetic subjects and controls. However, subgroup analysis suggested that (pre)diabetic conditions might accelerate decreases of Aβ1-42 but increase of t-Tau levels in the CSF of subjects with cognitive impairment, and the association with p-Tau in the CSF was stronger (P =0.001) for diabetes than those of pre-diabetes (P=0.61). Our analyses reveal that the relationship between (pre)diabetic conditions and AD-type biomarker status in the CSF was subjective to clinical characteristics.